2006
DOI: 10.1063/1.2219122
|View full text |Cite
|
Sign up to set email alerts
|

Light emission at 5V from a polymer device with a millimeter-sized interelectrode gap

Abstract: We report the onset of electrochemical doping and subsequent visible light emission at 5V and 360K from a planar light-emitting electrochemical cell with a 1mm interelectrode gap containing poly[2-methoxy-5-(2′-ethyl-hexyloxy)-1, 4-phenylenevinylene] (MEH-PPV), poly(ethylene oxide) (PEO), and XCF3SO3 (X=K,Li) as the active material. We rationalize the unprecedented low turn-on voltage of such wide-gap light-emitting electrochemical cells by demonstrating that the active material contains a mixture of crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 28 publications
5
52
0
6
Order By: Relevance
“…The measured ionic conductivity ͑ i ͒ for the active material is on the order of 10 −4 S cm −1 . 4,8 The electronic conductivity of doped PPVs ͑ doped ͒ can be as high as ϳ1 S cm −1 , 4,11-13 but the MEH-PPV material used here is amorphous, blended with an electrolyte, and not fully doped during doping-front progression and accordingly far from optimized from a conductivity perspective; thus, it is reasonable to expect that doped during doping-front progression is of the order of 10 −2 S cm −1 . The point at which the potential drop in the doped regions is the same as the drop over the undoped region can be estimated as follows: ͑a͒ Early in the process, the overpotential drops primarily over the undoped region where ion motion limits the current.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured ionic conductivity ͑ i ͒ for the active material is on the order of 10 −4 S cm −1 . 4,8 The electronic conductivity of doped PPVs ͑ doped ͒ can be as high as ϳ1 S cm −1 , 4,11-13 but the MEH-PPV material used here is amorphous, blended with an electrolyte, and not fully doped during doping-front progression and accordingly far from optimized from a conductivity perspective; thus, it is reasonable to expect that doped during doping-front progression is of the order of 10 −2 S cm −1 . The point at which the potential drop in the doped regions is the same as the drop over the undoped region can be estimated as follows: ͑a͒ Early in the process, the overpotential drops primarily over the undoped region where ion motion limits the current.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated temperature allows for a significant ionic conductivity in the active material, which in turn results in a low turn-on voltage and reasonably short turn-on time. 8 A computer-controlled source-measure unit ͑Keithley 2400͒ was employed to apply voltage and to measure the resulting current. The photographs of the doping progression were recorded through the optical window of the cryostat, using a digital camera ͑Canon EOS 20D͒ equipped with a macro lens, and under UV ͑ = 365 nm͒ illumination.…”
Section: A Lec Preparationmentioning
confidence: 99%
“…By heating these devices to a temperature of about 360 K, where differential scanning calorimetry shows that the PEO/salt phase transforms from predominately crystalline ͑with a low ionic conductivity͒ to amorphous ͑with a high ionic conductivity͒, the turn-on time decreases drastically ͑from several hours at 100 V when crystalline to six seconds at 50 V when amorphous͒. 28 Together with the results presented in this paper, this observation strongly suggests that it is the ion motion in the electronically insulating region that governs the propagation of the doping fronts during LEC turn-on.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27] Shin et al further developed this concept when they demonstrated that it is possible to turn on wide-gap devices at low voltages. 28 In this article, we employ this type of planar device to demonstrate that doping front propagation ͑or turn-on time͒ in LECs is limited by ion motion in the undoped region, and consequently that a significant electric field is located in this undoped region between the two doping fronts during the turn-on process. The resulting model not only predicts the turn-on time, but also explains the high aspect ratio fingers often observed in photographs of wide-gap devices under operation, which under some conditions are suspected of short-circuiting the anode and cathode resulting in device failure.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] These ions rearrange during operation, which in turn allows for a range of attractive device properties, including low-voltage operation with thick active layers and stable electrode materials. [31][32][33][34][35][36] However, the further development of LECs is currently hampered by an inadequate understanding of the device operation. In fact, an active debate regarding the fundamental nature of LEC operation has continued for more than a decade, and two distinct models are competing for acceptance: the electrochemical doping model 18,32,[37][38][39][40] and the electrodynamic model 36,[41][42][43][44] .…”
mentioning
confidence: 99%